Liver fluke and schistosome cross-infection risk between livestock and wild mammals in Western Uganda, a One Health approach - Daisy Namirembe; Tine Huyse; Rapheal Wangalwa; Julius Tumusiime; Casim Umba Tolo (International Journal for Parasitology: Parasites and Wildlife)
Trematodiases strongly reduce the welfare of humans and animals causing a great decline in health and productivity. Insufficient data on the extent of trematode infection in definitive hosts and associated risk factors remain a great threat to its control. A cross-sectional study was conducted to establish the; prevalence of liver flukes and schistosomes in livestock and wild mammals and the socio-ecological risk factors associated with their spread. Fresh dung samples were collected opportunistically (n = 865) and examined using formal ether sedimentation and microscopy for parasite eggs. Twelve abattoir visits were conducted to examine the livers of animals killed for mature flukes. Key informants (n = 110) including farmers, butchers, game rangers, and herders were interviewed to document the socio-ecological risk factors. In the abattoirs, 57.1%(CI 0.422–0.712) of cattle were infected with Fasciola flukes and not sheep and goats. Cattle dung had the highest prevalence (56% CI 0.518–0.604) of Fasciola eggs, followed by sheep (50%, CI 0.319–0.681) and goats (28.2%, CI 0.218–0.353). Among wild mammals, hippos' dung (66%; 95% CI 0.53–0.777) had the highest prevalence of Fasciola followed by warthogs (8%; 95% CI 0.002–0.385) and baboons (6.7%; CI 0.002–0.319). No Fasciola eggs were observed in elephant dung (n = 21) and monkeys (n = 2). Schistosoma bovis was found in cattle dung from Mpeefu (2.6%; 95% CI 0.007–0.066) and Ndaiga (4.3%; 95% CI 0.022–0.075) while S. mattheei in goats’ (1.4%; 95% CI 0.00–0.075) and cattle (0.39%; 95% CI 0.00–0.021) dung samples from Ndaiga. Key informants had moderate knowledge of fasciolosis (62.7%), highest among butchers (89.7%), and lowest among herders (31.8%). Only veterinary officers knew about schistosomiasis in animals. Free-range grazing and unsafe water sources for livestock, shared with wild animals, were the risky practices by most farmers (66–100%). Fasciola was prevalent in livestock and wild mammals, while Schistosoma in cattle and goats.